Comparative effects of sports massage and foam rolling on muscle recovery in university level futsal players / Husna Yunus ... [et al.]. - Yunus, Husna; Mohamed, Muhamad Noor; Azreen, Noor Azila; Raja Hussein, Raja Nurul Jannat; Safiq, Muhamad; Abu Kassim, Nurul Ain; Adnan, Muhamad Aizzat; Shaari, Maisharah; Mazaulan, Mardiana (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Muscle soreness is a common challenge among futsal players, impacting performance and recovery. This study evaluates the effectiveness of sport massage (SM) and foam roller (FR) techniques in reducing muscle soreness and compares their efficacy. Addressing gaps in recovery strategies, particularly for futsal players, this research provides insights into evidence-based practices for optimized recovery. Ten futsal players from UiTM Negeri Sembilan, with at least six months of consistent training, were selected. Participants underwent 15-minute SM and FR sessions targeting quadriceps, hamstrings, adductors, gluteus, and gastrocnemius muscles. Muscle soreness was measured using the Sit-to-Stand test (pain scale), knee extensor (pain scale), and knee flexion range of motion (goniometer) at five intervals: pre-training, immediately post-training, 24-, 48-, and 72-hours post-training.